Green technology in language teaching and learning for sustainable environment: A review study - Seraj Prodhan Mahbub Ibna (BIO Web of Conferences)
Nowadays, Technology is commonly used in language classrooms for learning and teaching. As teachers get assistance and make language classes real, so do learners. On the other hand, keeping the environment clean and fresh for future generations is one of the time- demanding concepts for using technology as environment-friendly in language classrooms. Thus, this systematic review paper will investigate how the conceptual framework of green technology materializes in language classrooms by researchers and leave insights for further research. To do this, the researcher investigated published research works in Google Scholar, Scopus, Emerald, and ScienceDirect. The results of this study identified different conceptual frameworks for integrating green technology in language pedagogies, e.g., Green Social Media in Language Teaching (GSMLT) and Green Language Teaching Approach (GLTA). Context‐ aware ubiquitous language learning (CAULL), Green Pedagogy (GP), Project-based Language Learning with Technology (PBLLT), Green Screens (GS), and Online Language Pedagogy (OLP). The findings also emphasized increasing awareness of GT among ELT stakeholders. In a nutshell, the study's findings will contribute to the literature on GT in ELT (English language teaching and learning).